L'Allemagne unie entre l'Ouest déclinant et l'Est désintégré - Létourneau, Paul (Études internationales, 1992)
German unification is both a cause and an effect of the restructuring of alliances now taking place with the end of the long postwar era. An enlarged Germany finds itself in a new geostrategic position at the centre of a henceforth unified continent and its vocation is pan-European. The underpinnings of its external policy and its security have been modified. In this context, the German government has opted not only for keeping a renewed NATO but also for deepening and widening Europe's economic and political institutions. It does not want to disappoint either the Americans or its European Community partners and those wishing to join the EC. Nor does it want to disappoint the East Europeans, including those-of the former Soviet Union. Nevertheless, the traditional policy of seeking non-isolation, at times not without ambivalence, is destined to change and could become more assertive. Two items testify to this change in direction : the "debate over normalization', which has brought down taboos in Germany, and the leadership role that Bonn has openly taken, for the first time since 1945, on the issue of recognition without further delay of Slovenia and Croatia by the European Community as of January 15 1992.